Faktor-Faktor Yang Mempengaruhi Profitabilitas Perusahaan Textile dan Garment yang Terdaftar di BEI Periode 2016-2021 - Sony Mardiko Putro; Indra Lila Kusuma; Suhesti Ningsih (Nur Science Institute, 2022)
The purpose of this study was to determine the effect of cash turnover, accounts receivable turnover, inventory turnover, and leverage on the profitability of textile and garment companies listed on the IDX in 2016-2021. In this study, researchers used secondary data with descriptive analysis methods, classical assumption test (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test) and hypothesis testing using multiple linear regression analysis, F test, t test, and R² test. The number of samples used as many as 30 data companies listed on the Stock Exchange using purposive sampling method. The results showed that simultaneously cash turnover, accounts receivable turnover, inventory turnover, and leverage had a significant effect on the profitability of textile and garment companies in 2016-2021. Partially, cash turnover and leverage have a significant effect on the profitability of textile and garment companies in 2016-2021, while accounts receivable turnover and inventory turnover have no significant effect on the profitability of textile and garment companies in 2016-2021.